Implicit motor learning in children with autism spectrum disorder: current approaches and future directions - Zheng, Weiqi (Frontiers in Psychiatry, 2024)
Motor dysfunction is increasingly being viewed as a core characteristic of autism spectrum disorder (ASD) in children. In particular, children with ASD have difficulty in learning new motor skills and there is a need to develop effective methods to improve this. Previous research has found that children with ASD may retain the ability to implicitly learn motor skills in comparison to their explicit learning of motor skills, which is typically impaired. This literature mini review focuses on summarizing the study of implicit learning in the acquisition of motor skills in children with ASD. First, we briefly introduce several common implicit learning methods in children's motor skill learning. Second, we focus on the role of two important implicit learning approaches in motor skill learning, namely, an external focus of attention and analogy learning. Finally, based on our review of the existing studies, we present an outlook for future research and the areas that need to be improved in the practical teaching of implicit learning in the acquisition of motor skills in children with ASD.Recently, research around autism has made great strides over the past decade in moving away from a medical deficit model to a neuro-divergent model that accounts for processing differences in the